If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 2 + -6 = 6x Reorder the terms: 2 + -6 + x = 6x Combine like terms: 2 + -6 = -4 -4 + x = 6x Solving -4 + x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -4 + x + -6x = 6x + -6x Combine like terms: x + -6x = -5x -4 + -5x = 6x + -6x Combine like terms: 6x + -6x = 0 -4 + -5x = 0 Add '4' to each side of the equation. -4 + 4 + -5x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -5x = 0 + 4 -5x = 0 + 4 Combine like terms: 0 + 4 = 4 -5x = 4 Divide each side by '-5'. x = -0.8 Simplifying x = -0.8
| 7x-6-(8-2)= | | And+6a= | | 11+7=6x+7 | | 17-(6X-7)=6X | | 3(2a+2)-4(3a-5)= | | 7x-9-9x=6x+12 | | -5A+10=5 | | -2A+1=4 | | 3a+1=2x+4 | | 4=2x-10 | | y=(x-3)(x-3)+(x-9)(x-9) | | 3/4x=7/1 | | 6.5/500= | | -3+A=2 | | 6(7d-12)=30 | | 4n=6.58 | | 28y+4=0 | | z/8-5=5 | | 6-3(x+10)=-5 | | ln(e)=0.3ln(x) | | (X^2-4)(x^2-4)=127449 | | 8x-7=59 | | -A-1=-3 | | 8*m*n*7*m*m*n= | | y=(x+1)(x+3)(x-4) | | (x)(x)+14x=0 | | 3(8+6y)=2(9y-12) | | 8mn*7m*7mn= | | Xsquared+14x+c=0 | | 3x+X=7 | | 4(3x+7)=2(6x+14) | | 7xw*2w= |